Real-World Treatment of Enterococcal Infections with Daptomycin: Insights from a Large European Registry (EU-CORE) - Lübbert, Christoph (Infect Dis Ther, 2015)
INTRODUCTION: Evolution of antibacterial resistance in pathogenic enterococcal strains poses a growing therapeutic challenge. Daptomycin, a cyclic lipopeptide, exhibits broad antibiotic activity against Gram-positive bacteria. METHODS: The European Cubicin(®) Outcomes Registry and Experience, a multicenter, retrospective, non-interventional study, recorded clinical outcomes following daptomycin treatment. RESULTS: Overall, 472 patients (predominantly elderly Caucasian males) were treated for enterococcal infections. Of those, 72.7% received antibiotics prior to daptomycin treatment, whereas 77.1% received other antibiotics concomitantly. Failure of previous therapy, resistant or non-susceptible pathogen, and narrowing of antibiotic therapy were the main reasons for switching to daptomycin treatment. Nosocomial infections comprised 55.8% of the cohort. Bacteremia (29.9%), complicated skin and soft tissue infection (29.2%) and endocarditis (12.3%) were the most common primary infections. Clinical success was achieved in 77.1% of patients, with similar success rates across all primary infection categories. The overall clinical success rate was marginally higher (82.5% vs 74.6%, p = 0.09) with daptomycin use as first-line versus second-line therapy. Patients receiving higher doses of daptomycin exhibited the highest clinical success rates (85.7% for ≥8 mg/kg/day vs 75.8% for <8 mg/kg/day, p = 0.08). While 81 (17.2%) patients reported at least one adverse event (AE), only 11 (2.3%) and 3 (0.6%) had treatment-related AEs and serious AEs, respectively. Separate microbiologic findings from Leipzig University Hospital demonstrate small proportions of Enterococcus faecium isolates with daptomycin minimum inhibitory concentrations = 4 mg/L (4%) or ≥8 mg/L (0.8%), which are regarded as non-susceptible. CONCLUSION: For enterococcal infections, daptomycin appears to be an effective and well-tolerated treatment option, exhibiting highest clinical success rates at higher doses. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s40121-015-0072-z) contains supplementary material, which is available to authorized users.